PENGARUH METODE SHOW AND TELL TERHADAP KETERAMPILAN BERPIDATO DENGAN TEMA CINTA TANAH AIR SISWA KELAS V SEKOLAH DASAR - Salsabila, Safira; Armariena, Dian Nuzulia; Marleni, Marleni (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to develop students’ speaking and public speaking skills in Indonesian language learning through the Show and Tell method. The research employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent control group design with a posttest-only format. The study was conducted at SD Negeri 196 Palembang involving fifth-grade students, with a total of 48 participants from classes V.A and V.B selected using a saturated sampling technique. Data analysis techniques included normality testing, homogeneity testing, and hypothesis testing. The results of the dependent sample t-test showed a significance value of Sig. (2-tailed) = 0.000 < 0.05 and a calculated t-value greater than the t-table value. This indicates that the null hypothesis (H?) was rejected and the alternative hypothesis (H?) was accepted. Thus, it can be concluded that the Show and Tell method has a significant effect on improving public speaking skills, particularly in the theme of “Love for the Homeland,” among fifth-grade students at SD Negeri 196 Palembang.